Graft Polymerization of Polyacrylonitrile or Poly(methyl methacrylate) onto Polyurethane for the Improvement of Mechanical Properties and Water Vapor Permeability. (28th April 2015) - Chung, Yong‐Chan; Kim, Ha Youn; Choi, Jae Won; Chun, Byoung Chul
<x xml:space="preserve">Abstract</x> Polyurethane was graft‐polymerized with poly(acrylonitrile) or poly(methylmethacrylate) to form the urethane‐acrylate polymers that demonstrated a significant improvement in tensile strength and the better low‐temperature flexibility. The water permeability was also increased if poly(methylmetacrylate) was grafted.